2019
DOI: 10.1101/847954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time is vision: functional preservation and enhanced capacity for recovery in subacute occipital stroke

Abstract: One Sentence Summary: The first 3 months after an occipital stroke are characterized by a gradual -not sudden -loss of visual perceptual abilities and increased rehabilitative potential if visual discrimination training is administered in the blind field. Abstract:Stroke damage to the primary visual cortex (V1) causes a loss of vision known as hemianopia or cortically-induced blindness (CB). While early, spontaneous, perimetric improvements can occur, by 6 months post-stroke, the deficit is considered chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Our current report builds upon our previous report on retinal neurodegeneration following thalamic infarction (Ye et al, 2022) and the fundamental observations that such retrograde transsynaptic neurodegeneration after visual pathway insult follows a distinct time course and pattern (Jindahra et al, 2012;Saionz et al, 2020;Fahrenthold et al, 2021). This study showed that the LI value, which indicates the shrinkage extent of the optic tract (Bridge et al, 2011;Millington et al, 2014;Fahrenthold et al, 2021), altered distinctly compared with age-sex matched stroke-free controls.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our current report builds upon our previous report on retinal neurodegeneration following thalamic infarction (Ye et al, 2022) and the fundamental observations that such retrograde transsynaptic neurodegeneration after visual pathway insult follows a distinct time course and pattern (Jindahra et al, 2012;Saionz et al, 2020;Fahrenthold et al, 2021). This study showed that the LI value, which indicates the shrinkage extent of the optic tract (Bridge et al, 2011;Millington et al, 2014;Fahrenthold et al, 2021), altered distinctly compared with age-sex matched stroke-free controls.…”
Section: Discussionsupporting
confidence: 77%
“…Time since stroke onset (months) and National Institute of Health Stroke Scale (NIHSS) scores were also documented. Since it has been well recognized that the process of TRD is time-dependent (usually occurring significantly from 3 to 7 months to the first few years maximally) (Jindahra et al, 2012), along with the expansion course of poststroke visual deficit, which becomes steady after 6 months (Cavanaugh and Huxlin, 2017;Wang et al, 2017;Saionz et al, 2020), in the following analysis we divided our patients into two subgroups: Group 1 (≤ 6 months) and Group 2 (>6 months). Visual acuity (VA) under illumination was completed for each eye using Snellen charts by an experienced neuro-ophthalmologist (WK) and later converted to the logarithm of the minimum angle of resolution (LogMAR).…”
Section: Study Populationmentioning
confidence: 99%
“…Aside from improving our scientific understanding of the neural mechanisms underlying visual recovery in CB, our findings are of vital importance for the development of more principled, customized, clinical neurorehabilitation therapies, adapted to the increasing number of people who suffer from cortically-induced visual impairments. Targeting blind-field regions with spared V1 activity might substantially improve the benefits of visual restoration training, particularly in subacute post-stroke periods (i.e., first 3 months) during which our training paradigm can substantially enhance capacity for recovery and preserve visual functions (Saionz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…CB subjects were trained at select blind-field locations on coarse (left-right) direction discrimination of random dot stimuli and/or vertical-horizontal orientation discrimination of static Gabor patches (Table 1 and Fig.1). For details about the training, testing stimuli and tasks, see our published studies Cavanaugh et al, 2015;Das et al, 2014;Huxlin et al, 2009;Saionz et al, 2019). Training was started at visual-field locations where discrimination performance on either task first dropped to chance (50% correct) during blind-field border mapping (i.e., in lab with online fixation monitoring using an infrared eye tracker [Eyelink 1000 or ISCAN RK464] interfaced with our psychophysical software, to ensure gaze-contingent stimulus presentation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation